Komodifikasi TikTok sebagai Media Komunikasi Politik Calon Presiden Tahun 2024 - Mei Candra Mahardika; Eny Susilowati (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The largest democratic event in Indonesia is the presidential election. The 2024 election will be even more exciting, thanks to social media campaigns. TikTok is one of the most popular social media platforms among young people. The TikTok phenomenon began in 2018 as an entertainment medium but received negative responses. TikTok, whose users are mostly young people, began to be used for campaign purposes. Through a systematic literature review and literature study, the purpose of this research is to explain how TikTok was commodified in its function in the 2024 presidential election. Research results from pintarpolitik.com and detikcom show that TikTok is a political force and a platform for political activity because its messages spread quickly and short videos are easily accepted by the public. Detikcom explains that during the election campaign period, posts on TikTok influenced political views and support for presidential candidates. Detikcom's TikTok user data shows that 41.26% of TikTok users in Indonesia are aged 18-24. The commodification of TikTok in Vincent's political economy theory can be found through content from a medium of expression to a political medium, which has undergone a change in value from an entertainment medium to an economic medium and has a role in the psychological values of society that determine the choice of presidential candidates in the 2024 election.